Moderating effects of gender and family responsibilities on the relations between work-family policies and job performance - Medina-Garrido, José Aurelio; Biedma-Ferrer, José María; Ramos-Rodríguez, Antonio Rafael (International journal of human resource management, 2021)
This study analyzes the impact of work-family policies (WFP) on job performance, and the possible moderating role of gender and family responsibilities. Hypothesis testing was performed using a structural equation model based on a PLS-SEM approach applied to a sample of 1511 employees of the Spanish banking sector. The results show that neither the existence nor the accessibility of the WFP has a direct, positive impact on performance, unlike what we expected, but both have an indirect effect via the well-being generated by these policies. We also find that neither gender nor family responsibilities have a significant moderating role on these relations, contrary to what we initially expected.